Emerging trends in the sea state of the Beaufort and Chukchi seas. (September 2016) - Thomson, Jim; Fan, Yalin; Stammerjohn, Sharon; Stopa, Justin; Rogers, W. Erick; Girard-Ardhuin, Fanny; Ardhuin, Fabrice; Shen, Hayley; Perrie, Will; Shen, Hui; Ackley, Steve; Babanin, Alex; et al.
Highlights: The seasonal extent of open water in the Arctic is increasing. The sea state is increasing in concert with the open water. Waves are larger and peak wave periods are longer. The additional wave energy is mostly directed at the coast (as opposed to the ice). Abstract: The sea state of the Beaufort and Chukchi seas is controlled by the wind forcing and the amount of ice-free water available to generate surface waves. Clear trends in the annual duration of the open water season and in the extent of the seasonal sea ice minimum suggest that the sea state should be increasing, independent of changes in the wind forcing. Wave model hindcasts from four selected years spanning recent conditions are consistent with this expectation. In particular, larger waves are more common in years with less summer sea ice and/or a longer open water season, and peak wave periods are generally longer. The increase in wave energy may affect both the coastal zones and the remaining summer ice pack, as well as delay the autumn ice-edge advance. However, trends in the amount of wave energy impinging on the ice-edge are inconclusive, and the associated processes, especially in the autumn period of new ice formation, have yet to be well-described by in situ observations. There is an implicit trend and evidence for increasing wave energy along the coast of northern Alaska, and this coastal signal is corroborated by satellite altimeter estimates of wave energy.